Порівняльний аналіз досвіду та можливостей видобутку метану вугільних родовищ у різних країнах світу - Lyashenko O.F.; Liashenko D.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2007)
Geological conditions of adjournment and distribution of methane in Ukrainian coal deposits are described, opportunities and experience of extraction of methane in Ukraine and other countries of the world are analyzed.